2007
DOI: 10.1111/j.1365-3156.2006.01809.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and associated morbidity of scabies in a rural community in Alagoas, Brazil

Abstract: Scabies is associated with considerable morbidity in this endemic community. Predilection sites, clinical presentation, quantity of skin surface affected and proportion of secondary infected lesions show a dichotomy between children and adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
81
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(94 citation statements)
references
References 38 publications
12
81
1
Order By: Relevance
“…7,11 In our study, in which dermatologists performed a careful clinical examination of the entire body, we confirmed the importance of burrows as a useful sign; we observed it in ∼3 of 4 patients regardless of their age. Nodules were also common, although they appeared in different locations according to age; for example, from 40% in adults with a genital preponderance to 60% in infants, especially in axillary and back locations (Fig 1 A and B).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…7,11 In our study, in which dermatologists performed a careful clinical examination of the entire body, we confirmed the importance of burrows as a useful sign; we observed it in ∼3 of 4 patients regardless of their age. Nodules were also common, although they appeared in different locations according to age; for example, from 40% in adults with a genital preponderance to 60% in infants, especially in axillary and back locations (Fig 1 A and B).…”
Section: Discussionsupporting
confidence: 61%
“…The clinical presentation of scabies has been mainly studied in patients from the developing world in whom clinical features may differ from those observed in patients from Western countries. 7 Indeed, in these countries from the developing world, scabies is often endemic, chronic, and frequently complicated by superinfections that may overlap with and obscure the specific clinical signs of scabies.…”
Section: Discussionmentioning
confidence: 99%
“…Usha et al, found that 25% of patients out 40 patients treated with ivermectin had secondary infection. 8,5 The secondary infection (pustules) in this study (59.5%) was more compared to (25%) in Usha et al study. 5 This may be because of the low education level, overcrowding, unhygienic condition, lack of awareness in our patients compared to Kerala were the study was conducted by Usha et al 5 …”
Section: Type Of Lesionscontrasting
confidence: 41%
“…The clinical consequences of secondary bacterial infection, especially with group A streptococci, result in significant, frequently unrecognized illnesses, such as cellulitis, boils, pyomyositis, lymphangitis and generalized lymphadenopathy. 19 It has been estimated that 300 million people suffer from scabies infestation at any one time 20 although this number has been disputed. 21 The associated morbidity was frequently underestimated.…”
Section: Discussionmentioning
confidence: 99%
“…10 Comparisons over time of the global burden of diarrheal diseases have revealed secular trends and demonstrated the impact of public health interventions. 19 A review of the incidence and prevalence of acute gastrointestinal illness from 33 studies in developed countries reported it to be ranging from 0.1 to 3.5 episodes per person-year. 12 It has been estimated that 5.3 million deaths attributable to CVD occurred in the developed countries in 1990, whereas the corresponding figure for the developing countries ranged between 8 to 9 million 13 Hearing loss is a significant health problem in developing countries.…”
Section: Discussionmentioning
confidence: 99%